Pengembangan Busy Book Berbasis Nilai Agama Dan Moral Untuk Pengenalan Pendidikan Seks Pada Anak Usia Dini - Faizatul Faridy; Nurul Izzati (Universitas Islam Lamongan, 2025)
This study departs from the vulnerability of young children to sexual violence/abuse and the persistent taboo on sex-related discussions in early childhood education settings (PAUD), which necessitates concrete, engaging, and religion-aligned learning media to strengthen child protection. The study aims to develop and evaluate the feasibility of a religion- and morality-based busy book for introducing sex education to children aged 5–6 years. An R&D design using the ADDIE model was implemented at PAUD Faza Al-Khalil (Aceh Besar) with 10 child participants; assessments comprised material-expert validation, media-expert validation, and classroom practicality observations. The results indicate 80% feasibility for content (feasible), 88% for media (highly feasible), and 83% practicality (Very Well Developed category). Children showed improvements in naming private body parts and distinguishing acceptable versus unacceptable touch. It is concluded that the religion–moral value-based busy book is feasible and practical for introducing sex education in PAUD, with novelty in the explicit integration of values into kinesthetic tasks that connect knowledge to courteous habits.